1979
DOI: 10.1111/j.1520-6378.1979.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment in Visual Scaling of Small Color Differences*

Abstract: Under the auspices of the ISCC Committee on Color Difference Problems, an experiment was carried out in the visual scaling of small color differences involving six color microspaces. The object‐color samples were visually evaluated by ranking, by subjective estimation, and by acceptability judgments. Visual scales were calculated by traditional procedures. Correlations were calculated between the visual scales and four color‐difference formulas (CIELAB, C1ELUV, FMC‐2, and FCM), and ellipsoids were optimized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…While a change in the color of S-G and S+G staining techniques ranged from 0.73 to 1.06. The S+G group has the highest color change value in citric acid solution with the level of 1.06 ± 0.11 which could be detected by an eye of a trained person (41). The result corresponded with an in vitro study of Vichi et al using spectrophotometer with gray card to measure the color change of resin composite (42) which showed that the ∆E values between 1 -3.3 can be perceived by human eye, but clinically acceptable.…”
Section: Color Changesupporting
confidence: 76%
“…While a change in the color of S-G and S+G staining techniques ranged from 0.73 to 1.06. The S+G group has the highest color change value in citric acid solution with the level of 1.06 ± 0.11 which could be detected by an eye of a trained person (41). The result corresponded with an in vitro study of Vichi et al using spectrophotometer with gray card to measure the color change of resin composite (42) which showed that the ∆E values between 1 -3.3 can be perceived by human eye, but clinically acceptable.…”
Section: Color Changesupporting
confidence: 76%
“…Studies that show no difference was seen between the try-in paste and matching cements in terms of color perception are similar to the findings of the current investigation. 33,34 Research [35][36][37] investigating the impact of ceramic thickness on the compatibility of the try-in paste and its corresponding resin cement has shown that the thickness of the ceramic material has a noticeable influence on this compatibility. However, the ΔE values between the try-in pastes and resin cements have been found to increase with decreasing ceramic thickness, suggesting a decline in compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…The human eye could detect the difference in color when ∆E* is above 1.0. 41 However, Ruyter et al reported that ∆E* above 3.3 was unacceptable in dentistry 42 . In this study, color change of M0 group was the highest while all PMMA/PLA blend ratios showed no signi cant difference in color stability, compared to PMMA.…”
Section: Discussionmentioning
confidence: 99%